2010
DOI: 10.4269/ajtmh.2010.09-0022
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of the MSP1 Genes from Plasmodium malariae and Plasmodium ovale

Abstract: The merozoite surface protein 1 (MSP1) is the principal surface antigen of the blood stage form of the Plasmodium parasite. Antibodies recognizing MSP1 are frequently detected following Plasmodium infection, making this protein a significant component of malaria vaccines and diagnostic tests. Although the MSP1 gene sequence has been reported for Plasmodium falciparum and Plasmodium vivax, this gene has not been identified for the other two major human-infectious species, Plasmodium malariae and Plasmodium oval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
38
0
5

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(51 citation statements)
references
References 41 publications
(49 reference statements)
8
38
0
5
Order By: Relevance
“…For P. relictum (SGS1), it was possible to identify the full 3′ end of the peptide; within this region the GPI anchor point was fully conserved at the amino acid level between P. falciparum , P. gallinaceum and P. relictum (SGS1) with the characteristic “FCSSS” motif (Figure 3). The “FCSSS” motif has been found to be extremely conserved across almost all investigated species of malariae parasites [27] and this was also the case when including more lineages of avian malariae species. In the p19 section of the avian malaria parasite peptides, it was also possible to identify the two epidermal growth factor-like domains (EGF), based on the six conserved characteristic cysteine residues [28] (Figure 3).…”
Section: Discussionmentioning
confidence: 89%
“…For P. relictum (SGS1), it was possible to identify the full 3′ end of the peptide; within this region the GPI anchor point was fully conserved at the amino acid level between P. falciparum , P. gallinaceum and P. relictum (SGS1) with the characteristic “FCSSS” motif (Figure 3). The “FCSSS” motif has been found to be extremely conserved across almost all investigated species of malariae parasites [27] and this was also the case when including more lineages of avian malariae species. In the p19 section of the avian malaria parasite peptides, it was also possible to identify the two epidermal growth factor-like domains (EGF), based on the six conserved characteristic cysteine residues [28] (Figure 3).…”
Section: Discussionmentioning
confidence: 89%
“…The assembled PmMSP - 1 sequences were 5160 bp (M0N00648) and 5150 bp (M0N00290 and M0N00556) in length, whereas the PoMSP - 1 sequences were both 5157 bp. Alignment of the PmMSP - 1 sequences with the full-length sequence of a Cameroonian isolate MM1A (GenBank #FJ824669) [45] revealed nucleotide and amino acid identities of ~98 and ~97%, respectively. Alignment of the PmMSP - 1 sequences from this study with the sequences of 11 Brazilian isolates by fragments showed that fragment 2 sequences corresponding to amino acids 637–858 in the MM1A sequence were the most polymorphic with 87.3–88.9 and 82.3–83.6% identities in the nucleotide and amino acid sequences, respectively (Additional file 4).…”
Section: Resultsmentioning
confidence: 99%
“…Insertions/deletions (indels) in coding regions were determined from multiple alignments of amino acid sequences to maintain the reading frame. Sequences of the two Cameroon isolates (GenBank accession numbers FJ824670 and FJ824671) were included for comparison [14]. Tandem repeats were detected by scanning the sequence with a small window, determining the distance between exact matches and testing the statistical criteria as implemented in the Tandem Repeats Finder version 4.0 program [18].…”
Section: Methodsmentioning
confidence: 99%
“…Recently, two nucleotide sequences of the gene encoding the merozoite surface protein-1 of P. ovale curtisi ( PocMSP-1 ) from Cameroon patients were determined [14]. However, the MSP-1 sequence of P. ovale wallikeri ( PowMSP-1 ) remains unknown.…”
Section: Introductionmentioning
confidence: 99%